2021
DOI: 10.11591/edulearn.v15i3.18934
|View full text |Cite
|
Sign up to set email alerts
|

Developing online learning guidebook for junior high school level in Kendari City

Abstract: This research aimed to develop online learning guidebook for junior high school level. The method used in this research was research and development in terms of 4-D model development which consists of four main stages: Define, Design, Develop, and Disseminate. The informants were study consisted of 2 expert informants and 17 junior high school teachers in Kendari City, Southeast Sulawesi, Indonesia. This type of research data was descriptive qualitative. The data collected were in the form of suggestions and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The development model used in this study is the development model developed by Thiagarajan, namely 4-D from the acronym define, design, development, and dissemination (Erfan et al, 2022;Fitri, 2019). The choice of the 4-D development model is because the development steps in the 4-D model are detailed, systematic, and easy to follow for each development procedure (Darnawati, Jamiludin, Mursidin, & Ili, 2021;Supartini, Weismann, Wijaya, & Helaluddin, 2020). Furthermore, Jatmiko & Fiantika (2017) The first stage of development, namely defining, aims to analyze the needs, materials, and characteristics of students needed to develop learning video products.…”
Section: Methodsmentioning
confidence: 99%
“…The development model used in this study is the development model developed by Thiagarajan, namely 4-D from the acronym define, design, development, and dissemination (Erfan et al, 2022;Fitri, 2019). The choice of the 4-D development model is because the development steps in the 4-D model are detailed, systematic, and easy to follow for each development procedure (Darnawati, Jamiludin, Mursidin, & Ili, 2021;Supartini, Weismann, Wijaya, & Helaluddin, 2020). Furthermore, Jatmiko & Fiantika (2017) The first stage of development, namely defining, aims to analyze the needs, materials, and characteristics of students needed to develop learning video products.…”
Section: Methodsmentioning
confidence: 99%
“…The learning process using virtual meeting applications without intensive accompaniment caused issues; one of those was difficulty understanding the content material [20], [21]. Students' difficulty in understanding concepts was caused by the lack of face-to-face interaction between students and lecturers and fellow students [22], [23] and the lack of lecturers' experience in implementing distance learning [24]. The arising obstacles indicated that students would not participate effectively in distance learning during the pandemic.…”
Section: Introductionmentioning
confidence: 99%